(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article provides detailed information about the principles of consciousness and activity of music teaching, scientific, systematic and continuity in music lessons, demonstrativeness in music lessons, comprehensive development of students’ cognitive powers in the lesson and consistency.